PENGARUH PENERAPAN AKUNTANSI BERBASIS AKRUAL, GOOD GOVERNANCE, DAN PENGAWASAN PENGELOLAAN KEUANGAN TERHADAP PENCEGAHAN FRAUD PADA KEUANGAN DAERAH - Nafisah, Maya Yulia; Witono, Banu (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the effect of accrual-based accounting implementation, good governance, and financial management supervision on fraud prevention in regional finances. This research method is quantitative with the type of causality research. The data collection technique used by researchers in this study was a questionnaire method.  The population in this study were subjects related to the research that the authors conducted at the secretariat of the Surakarta Privy Council. The sampling criteria set are employees or structural officials of the finance department who are in the secretariat of the Surakarta Keresidenan council. The sampling technique used is purposive sampling technique. The data source used by this researcher is primary data. Data analysis techniques are measured on a Likert scale using SPSS 20 software with data quality tests, classical assumption tests, and hypothesis testing. The results of this study are that the application of accrual-based accounting has a significant effect on fraud prevention both partially and simultaneously. Good governance has a significant effect on fraud prevention. Financial management supervision has no effect on fraud prevention